Refurnishing Homes in a Bombed City: Moral Geographies of the Utility Furniture Scheme in London. (2nd January 2021) - Reimer, Suzanne; Pinch, Philip
Abstract : The London Blitz was a catalyst for national state control of the entire commodity network for furniture; the only wartime commodity for which this was done. The Utility furniture scheme sought to manage material shortages and combat profiteering in the markets for new and second-hand furniture. It also responded to the vulnerability of the nation's furniture producers, which were disproportionately concentrated in and around London. Set against the immorality of indiscriminate bombing of civilian populations and illegal practices on the 'black market', the Utility scheme prescribed new moral geographies of equitable distribution based on need, of consumer rights protection, and of improvements to labour conditions and wages. The paper intervenes into debates about the social construction of moral geographies by examining the collective institutional response of the Utility scheme and the manner in which it sought to provision wartime homes.